Time of Pediatric Intensive Care Unit Admission and Mortality: A Systematic Review and Meta-Analysis - Williams, Vijai; Jaiswal, Nishant; Chauhan, Anil; Pradhan, Pranita; Jayashree, Muralidharan; Singh, Meenu (Journal of Pediatric Intensive Care, 2020)
The aim of this study was to determine the association between the time of admission (day, night, and/or weekends) and mortality among critically ill children admitted to a pediatric intensive care unit (PICU). Electronic databases that were searched include PubMed, Embase, Web of Science, CINAHL (Cumulative Index of Nursing and Allied Health Literature), Ovid, and Cochrane Library since inception till June 15, 2018. The article included observational studies reporting inhospital mortality and the time of admission to PICU limited to patients aged younger than 18 years. Meta-analysis was performed by a frequentist approach with both fixed and random effect models. The GRADE (Grading of Recommendations Assessment, Development, and Evaluation) approach was used to evaluate the quality of evidence. Ten studies met our inclusion criteria. Five studies comparing weekday with weekend admissions showed better odds of survival on weekdays (odds ratio [OR]: 0.77; 95% confidence interval [CI]: 0.60–0.99). Pooled data of four studies showed that odds of mortality were similar between day and night admissions (OR: 0.93; 95% CI: 0.77–1.13). Similarly, three studies comparing admission during off-hours versus regular hours did not show better odds of survival during regular hours (OR: 0.77; 95% CI: 0.57–1.05). Heterogeneity was significant due to variable sample sizes and time period. Inconsistency in adjusting for confounders across the included studies precluded us from analyzing the adjusted risk of mortality. Weekday admissions to PICU were associated with lesser odds of mortality. No significant differences in the odds of mortality were found between admissions during day versus night or between admission during regular hours and that during off-hours. However, the evidence is of low quality and requires larger prospective studies.
Keywords: pediatric; intensive care; critical care; time of admission; mortality